Participation of Leukotrienes in the Immune Modulation of Oral Tolerance - de Oliveira, Sandra R. P.; Nomizo, Auro; Frantz, Fabiani G.; Faccioli, Lúcia H.; Matos, Ana Paula Keller de; Carrilho, Emanuel; Afonso, Ana; de Freitas Anibal, Fernanda (Frontiers in Microbiology, 2017)
Oral tolerance is characterized as a peripheral immune tolerance form, in which, mature lymphocytes in lymphoid tissues associated with mucosa, become non-functional or hypo responsive due to prior oral administration of antigen. Oral tolerance is an important immunological phenomenon due to its therapeutic potential in inflammatory processes and others diseases. Here we evaluated leukotriene role in the induction of oral tolerance, as well as, the production of cytokines IL-5 and IFN-γ in leukotriene deficient animals (knock-out). Our results suggested that even in the presence of oral tolerance and leukotrienes absence, cytokine IFN- γ remains being secreted, which gives us an indication of immune system specificity and also that IFN-γ participates in various immune processes. Keywords: Oral tolerance, Leukotriene, Cytokines, Immune response, IL-5, IFN-γ